COMPARISON OF TEXT WRITING LEARNING REPORT OF EXPOSITION OBSERVATION AND TEXT RESULTS USING WEB-BASED STAD MODEL (PERBANDINGAN PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI DAN TEKS EKSPOSISI MENGGUNAKAN MODEL PEMBELAJARAN STAD BERBASIS WEB) - Nisja, Indriani; Mana, Lira Hayu Afdetis; Yusandra, Titiek Fujita (Jurnal Gramatika, 2019)
This study aims to describe the comparison of writing the report text of observations and exposition text using the web-based STAD model. This type of research is quantitative with the experimental method of Postest-Only Control Design. The sample of this study was 36 students of grade X MIPA 1 of SMAN 12 Padang. The results of the study using the web-based STAD model are for writing report text skills the results obtained an average score of 82.41 at a mastery level of 76-85% with Good qualifications (B) and exposition text writing skills gained an average score of 81.48 at a mastery level of 76-85% with Good qualifications. Based on the results of the t-test concluded that there is a comparison using the web-based STAD model because tcount> ttable (5.82> 1.68). So it can be concluded that web-based learning greatly affects student learning outcomes, especially in writing report texts on observations and expositions.